Lifetime productivity and repeatability estimation of selected traits of crossbred cows in Savar Dairy Farm - Islam, MS; Akhtar, A; Hossain, MA; Rahman, MF; Hossain, SS (Progressive Agriculture, 2018)
The study was conducted on 244 crossbred cows of (Central Cattle Breeding and Diry Farm), Savar, Dhaka to evaluate the effect of different productive groups on their lifetime performance of various productive traits using twenty years data. Data were accumulated from a prescribed data sheet maintained by Central Cattle Breeding Station, Savar, Dhaka. Genetic groups for this experiment were Local Friesian (LF), Local Jersey (LJ), Local Hariana X Friesian (LH x F), Local Friesian X Local Friesian (LF x LF) and Local Jersey X Local Jersey (LJ x LJ). The studied parameters were age at puberty, lactation length, lactation yield, total milking days, and total milk yield in lifetime. The data were analyzed using Least-Squares Mixed Model and Maximum Likelihood Computer Program (Harvey, 1990). Analysis showed that genetic groups had a significant effect on age at puberty, lactation length and lactation yield (P<0.01), total milking days and milk yield in lifetime (P<0.001). From the result it was found that earliest age at puberty were in L x F (749.27±99.01). Lactation length and standardized lactation yield were also higher in L x F (258.69±20.04 days and 1408.80±83.60 kg respectively). Total milking days and milk yield were observed higher in (LH x F) with mean of 1468.30±198.58 days and 7340.32±1813.28 kg, respectively. The repeatability estimates of lactation length for genetic groups LF, LJ, LH x F, LF x LF and LJ x LJ were 0.24±0.09, 0.04(-ve), 0.10±0.05, 0.07±0.05 and 0.49±0.22, respectively. The same for lactation yield was 0.17±0.08, 0.27± 0.02, 0.07±0.04, 0.17±0.08 and 0.03±0.05 respectively. From analysis it was revealed that in respect of productive performances the L x F genetic group was found superior compared to other groups but interns of total lifetime productivity, LH x F ranked the highest in the given environment. It is concluded that lifetime productivity needs to be considered as an appropriate guideline for selecting genetic groups for future productivity. Progressive Agriculture 29 (2): 168-177, 2018